PRODUCTIVITY GAP BY GENDER AMONG RICE FARMERS IN NORTH-CENTRAL NIGERIA - Sanusi Mohammed Sadiq; P I Singh; M M Ahmad (Agricultural Socio-Economics Journal, 2021)
The present research used a field survey data of 2020 rice cropping season to determine yield gap by gender among rice farmers in North-Central Nigeria. A total of 376 farmers were drawn from a sampling frame through a multi-stage sampling technique and a structured questionnaire coupled interview schedule was used for information elicitation. Both descriptive and inferential statistics were used for data analysis. The empirical evidences showed that most of the farmers have negative attitudes towards risk and this owes to poor resource capital base, thus hinders cultivation of economic holdings. Besides, women farmers were more averse to risk than the men farmers which owes largely to gender discrimination and stereotype induced by culture and religion, thus hindered their access to and control over productive resources. Furthermore, neither gender nor risk attitudinal differentials have impact on the average yield of the farmers. However, it was established that yield gap was largely due to gender and risk attitudinal discriminations. Therefore, the study enjoins the farmers, especially the women folk to harness social capital viz. participation in co-operative association- pecuniary advantages, thus enable them to have access to and control over productive. In addition, the policymakers are advised to create an enabling agricultural environment for the women folk viz. gender budget mainstreaming, thus tackling women farmers’ susceptibility to the vicious cycle of poverty.